Analysis and health risk assessment of toxic and essential elements of the wild fish caught by anglers in Liuzhou as a large industrial city of China. (March 2020) - Miao, Xiongyi; Hao, Yupei; Tang, Xing; Xie, Zhouqing; Liu, Liping; Luo, Shuwen; Huang, Qibo; Zou, Shengzhang; Zhang, Chunlai; Li, Jun
Abstract: Most wild fish caught by anglers (WFAs) are likely to be contaminated by toxic metals, particularly the fish collected from the waterways in urban and suburban areas; hence, the determination of health risk caused by WFAs consumption associated with toxic metals is vital. Therefore, Liuzhou, one of the largest industrial cities in China, was considered as an example city in this study. Eight toxic elements were analysed to uncover the pollution status and consumption safety of WFAs. Moreover, the suitable angling waterways were identified in the urban and suburban areas. The obtained results suggested relatively high concentrations of Zn, Cr and Cd, which were also found to be beyond corresponding Maximum Residue Limit. Among all analysed elements, only the mean pollution indices of Cr and Cd were observed to be beyond 0.2, revealing that the observed WFAs were generally contaminated by these metals. However, the potential health risk of WFAs can be predominately attributed to Cr, confirmed by the significantly higher Target hazard quotients (THQ). For adults, all the THQ values were below 1, indicating no significant health risk being associated with WFAs consumption in the case of adults. On the contrary, all the THQ values for Children were beyond 1, suggesting children being susceptible to great health risks due to WFAs consumption. Furthermore, the weekly recommended consumption of WFAs in urban area is remarkably lower than the current rate of fish consumption observed among urban residents; therefore, the waterways in urban areas can be evaded for fish angling. Graphical abstract: Image 10249 Highlights: Eight different metals were identified in the wild fish caught by anglers from Liuzhou region of China. Higher concentrations of metals were observed in the wild fish caught by anglers in urban area. Most wild fish caught by anglers were polluted by Cr and Cd. The wild fish caught by anglers are not safe for consumption by children. Angling activities should be restricted to be conducted away from the waterways in urban areas.